HUBUNGAN ANTARA BENTUK ARKUS KAKI TERHADAP KECEPATAN LARI PADA PEMAIN SEPAKBOLA USIA 11-14 TAHUN DI SEKOLAH SEPAK BOLA - Sekar Utami, Trie; BL, Abdurahman Berbudi; Sariana, Erna; Arya Pambudi, Restu (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Background: Running speed is a physical condition that must be owned by a football player. In process of improving achievement in football, its necessary to pay attention to things that affect running speed is the shape of the foot arch. The function of the arch of the foot is to hold bodyweight and movement. Methods: uses a cross-sectional with a total sample of 105 responden selected by proportional random sampling technique. Parameters using a 30-meter runningspeed test and measuring shape of the arch using the footprint then calculated with Clarke's angle method. Result: data was analyzed of corellateian rank spearmen showed a p-value (0.00<0.05) and r-value of -0.308 means the colleration is reasonably low between shape of the foot arch and running speed, in a negative direction. Conclusion: There is a significant relationship between the shape of the foot arch and runningspeed in soccer players aged 11-14years at the Soccer School.